Does Age of First Marriage Affect Stunting? (Ecological Analysis of the 2021 Family Data Collection and 2022 Nutritional Status Survey) - Ayudha, Mita Dwi; Herowati, Diyah Herowati; Rochmah, Thinni Nurul (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Adopting the WHO conceptual framework on stunting in children, the causes of stunting in growth and development are due to household and family factors, including maternal factors during pregnancy or before pregnancy, such as teenage pregnancy. This study uses the 2021 Family Data Collection (PK21) which has been verified and validated in 2022 (PK22), a census conducted by the Indonesian Population and Family Planning Agency . The prevalence of stunting uses data from the 2022 SSGI (Indonesian Nutrition Status Survey). To determine the relationship between age at first marriage and the prevalence of stunting, this study used 38 districts in East Java Province as the unit of analysis. Based on PK21 and verval data, families at risk of stunting are defined as families at risk of giving birth to stunted children. While the dependent variable is selected from data on the number of couples who meet the requirements who are married under age (under 19 years). This research is an observational research that is analytic in nature. Bivariate analysis was performed using Spearman's correlation analysis. From the results of the analysis it was found that there was a relationship between the prevalence of marriage age and the prevalence of stunting in East Java with a p value = 0.005. This means that the higher the prevalence of young marriages in a district, the higher the prevalence of stunting. Therefore, increasing the age of first marriage is a very important measure to end child marriage.